Decision support system in determining best sales using Simple Additive Weighting (SAW) method - Siti Anisah (Jurnal Mantik, 2023)
This research problem takes the case of a food menu, one of which is dumpling sales data under the auspices of CV. Ayu Megapolitan, the aim is to find out what menus consumers want in order to maximize production materials. Siomay sales data at CV Ayu Megapolitan requires a determination in the manufacturing process, so that it meets what consumers expect. The menu is: original siomay, fried siomay, soup siomay, chicken siomay. These variants are taken into account to determine the best variant according to sales data using the method to be used. The development method used is the Simple Additive Weighting (SAW) method by finding the weighted sum of the performance ratings for each alternative on all attributes. It is hoped that the results of this research will help in decision making to determine dumpling sales data